Pengaruh Project Based Learning disertai Know Want Learn Chart terhadap Keterampilan Berpikir Fluency, Flexibility, dan Originality Peserta Didik Biologi SMA Kelas X - Laksmi, Gardena Smoro; Probosari, Riezky Maya; Saputra, Alanindra; Widowati, Dewi (Bioedukasi: Jurnal Pendidikan Biologi, 2018)
ABSTRACT One of the goals of 21st century education is  forming creative students. Based on a survey of Global Creativity Index in 2015, creative thinking level of Indonesian students is low, which is ranked 86th out of 93 countries. Project Based Learning (PjBL) is learning model that is proven to be able to improve students' creative thinking skills but often requires a long duration. KWL Chart function is controling the learning process to be systematic and effective because the tasks performed by students become focus so that it can cover the shortcomings of PjBL. The distribution of values in the PjBL class with the KWL chart (experiment 1) and the PjBL class only (experiment 2) are more diffuse than the control class, it can be seen that the pretest as a covariate has less significance than the significance level of 0.05 which is equal to 0,000. It is stated that the pretest value and the posttest value are linear. There are other aspects outside of research that influence students' creative thinking skills. The obtained Squared R value is 0.560, it means that the difference in model and media integration given in the control class, experiment 1, and experiment 2 only affects 56% of students' creative thinking skills. Other factors outside of research that affect students' creative thinking skills are as much as 44%, even though the time needed for the experiment 1 class is shorter than the experimental class 2.